Natal qual é a sua cara?: análise do perfil edilício da avenida Eng. Roberto Freire (Natal/RN) à luz da acessibilidade - Nascimento, Rodrigo Costa do (2011)
This study focuses on the building ensemble of Avenida Roberto Freire, a main road in Natal, Brazil, as a material expression of the confluence of various factors among which the following may be emphasized: high level of accessibility due to urban spatial re-structuring and the growth of the real estate market, in view of the increasing number of consumers, who arrived in Natal within the last decades. The intense urban modification process that has been going on in Natal since at least the 1980s, has engendered the formation of long axial lines which express the expansion dynamics and some of the forces subjacent to it. Avenida Roberto Freire has been an iconic example of an urban thoroughfare where architecture becomes primarily a communication support that can be perceived by fast moving passers-by, what brings it close to the venturian concept of strip (Venturi at al, 1972). The building types that line the road not only respond to the dynamics in process but also contribute to intensify it, as they house a variety of uses which attract people and generate more movement. The dynamics is further strengthened by the action of the real estate business which benefits from the increase of highly accessible locations, and from the private and public investments and incentives to tourism that aim to insert this city into the globalized world. Although the intention of reconstituting part of the history of density increase on this avenue in a diachronical perspective was attempted within the limits of the available references and documentation, the central contribution of this study is to understand the relations between topological accessibility and the typological nature of the building ensemble. By observing the synchronic morphological frame resulting from the spatial configuration analysis pertinent to this avenue (cf. Hillier and Hanson,1984) and the inventory and classification of the building ensemble there existing, this study aims to understand how architecture responds to accessibility in view of the real estate pressure, boosted by a cosmopolitanizing process brought about by the continuous flow of foreign and Brazilian arrivals as visitors, temporary or permanent residents